Perancangan Dan Penyusunan Modul Dan Powerpoint Akuntansi Keuangan Kelas 11 Semester Genap Pada SMK Negeri 1 Tanjungpinang - Etalya Etalya (Universitas Internasional Batam, 2021)
Since Covid-19 happened, there has been a temporary closure of educational institutions as an effort to prevent the spread of the Covid-19 pandemic. Implementation of learning and teaching takes place online. Online learning activities using digital technology, then the teacher teaching system required to be more creative like make learning materials in PowerPoint and module. Practical work methods is using interviews and observations. Design and arrangement materials in PowerPoint and module based on the syllabus and “Kompetensi Inti dan Kompetensi Dasar” (KIKD) financial accounting lessons. The results of the materials that has been made in the module and PowerPoint can make it easier for teachers when teaching online and for students to learn. Expected the module and PowerPoint there will be a change for the better for adjustment of conditions in the next learning period.